Photo capturing using colorimage processing (PCCIP) - Tan, Khai Shuen (2011)
Photo Capturing using Color Image Processing (PCCIP) is a prototype developed to capture an image with color tracking methods. The prototype developed is able to identify and track two similar color markers which attach at user finger as an identifier.With the identification of the position of the markers,within a certain wait time, the prototype will call a capture function which will capture an image cover inside the color marker boundary.One of the main objectives in the development of PCCJP is to implement color image processing methods in touch less technique,means capture an image based on the detection of color marker, without any body interaction between user and the hardware device. In line with the development of technology,Human Computer Interactions (HCI)is more emphasize and that is why PCCIP was developed to introduce a new interactions way between human and devices.Evolutionary methodology was implemented in the development of PCCIP,through several image processing techniques include image acquisition, image enhancement, image features extraction, image segmentation and object recognition. Ninety samples were tested and the result shown that 90% of the sample has successfully passed from the testing phase.This shown that the developed prototype has met it objective. Therefore,the result indicates that the implementation of color processing techniques in touch less methods was successful to create a new human computer interactions method.